Dampak Pemupukan Si Plus Terhadap Pertumbuhan, Produksi dan Nilai Nutrisi Rumput Brachiaria Mulato pada Defoliasi Kedua - Uhud Abdullah; Yusuf Akhyar Sutaryono; Imran Imran (Faculty of Animal Husbandry, University of Mataram, 2016)
The study aimed to assess the impact of Si Plus fertilization on the growth, production and nutritional value ofgrass Brachiaria Mulato on second defoliation. This study uses a randomized complete design with fourtreatments, P1: grass given fertilizer silicate plus on day 10 and 20, P2: grass given fertilizer silicate plus ondays 10, 20 and 30, P3: grass given fertilizer silicate plus on day 10, 20, 30, and 40, after the firt defoliation.Parameters measured were grass growth include: plant height, leaf number and the number of tillers, plantproduction will be calculated after the crop is harvested that at the age of 120 days (second defoliation). Thenutritional value is the proximate and the digestibility in vitro. The results showed the content of dry matterl,crude lipid, crude protein, crude fiber and digestibility of dry matter and organic matter digestibility in thesecond defoliation showed no significant differences for spraying Si Plus with different intensities. It wasconcluded that spraying fertilizer Si Plus does not affect the growth, production, nutritional value and in-vitrodigestibility of grass Mulato on defoliation II